PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI) - Mardani, Ronny Malavia (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2011)
The objective of this study is to analyze the influence of Intellectual Capital to Corporate Finance Performance. Based on the result of this study, show that : a) There is a positive influence of Intellectual capital (VACA, VAHU, and STVA) to the company's financial performance (Return on Equity, Return on Total Assets, Asset Turn Over, and Growth Revenue).; b) There is a positive influence of Intellectual capital (Vaca, VAHU, and STVA) to the future of company's financial performance, and c) There is a positive influence of average growth of the Intellectual Capital to the future company's financial performance.. Â